Hubungan Kebiasaan Mengonsumsi Makanan Cepat Saji dengan Indeks Massa Tubuh pada Mahasiswa Fakultas Kedokteran Ukrida Angkatan 2016 Periode September 2017 - Vina Cyrilla; Gracia JMT Winaktu; Susanty Dewi Winata (Jurnal Kedokteran Meditek, 2018)
Globalization and urbanization have a considerable impact in eating habits. These have caused many people eat fast food which contains high calories and low nutrition. Eating fast food has become a risk factor for obesity. This study was a cross-sectional analytics study which was conducted in September 2017. Subjects of 85 active students of the 2016 batch from faculty of medicine Ukrida were selected by a simple random sampling. The study found that among the surveyed students, 37.6% rarely ate fast food, whereas 62.4% usually ate fast food. The chi-square analysis obtained a p value of 0.000 which indicated that there was a relationship between fast food consumption habit with Body Mass Index. It was also found that age and gender didn’t have relationship with Body Mass Index.Keywords: habit of consumption, fast food, body mass index